ETHNIC PROCESSES IN THE KASHKADARYA OASIS IN THE LAST MIDDLE CENTURIES (IN THE EXAMPLE OF THE CITY OF KARIS) (Uzbek Scholar Journal, 2025)
This article analyzes the ethnic processes that took place in the city of Karshi in the late Middle Ages, the ethnic groups and clans that lived in this city, the ethnic composition of the nomadic and settled population, the process of settlement, their language and dialect, and the role of the large clans of the Mangit and Kenagas clans in the political life of the Bukhara Emirate, based on historical sources.